Abnormal cervical cytology following large loop excision of the transformation zone: a case controlled study - Shafi, M I; Dunn, J A; Buxton, E J; Finn, C B; Jordan, J A; Luesley, D M (British journal of obstetrics and gynaecology, 1993)
To determine factors that may predict cytological outcome at 6 months following large loop excision of transformation zone (LLETZ) for cervical intra epithelial neoplasia (CIN) and to investigate the outcome in women with continuing cytological abnormality. Case controlled retrospective study. Dudley Road Hospital, Birmingham and Midland Hospital for Women. Fifty-eight women with abnormal follow up cytology and a control group of 116 women. The relation between pretreatment and treatment factors and cytological outcome, and the relation between cytology and histology in women who had biopsies for persistent abnormal cytology. Univariate and stepwise logistic regression analysis showed that the number of sectors of atypical transformation zone (lesion size) and the excision margin status of the large loop excision specimen are of prognostic importance for the prediction of cytological abnormality at the 6 month follow up visit. Sixteen women have undergone further cervical biopsy. Of the five cases of persistent CIN, four had cytological changes showing moderate or severe dyskaryosis. Of the 11 women with koilocytosis or normal histology, 10 had mild dyskaryosis or borderline changes on their follow up cytology. Lesion size and excision margin status are important correlates of follow up cytology when treating patients for CIN with LLETZ. All women with abnormal cervical cytology at follow up should undergo colposcopic assessment. Excision biopsy is indicated if follow up cytology shows moderate or severe dyskaryosis, especially if still present 12 months after treatment.